Growth Spillover Effects and Regional Development Patterns : The Case of Chinese Provinces - Luo, Xubei (World Bank, Washington, DC, 2012)
The author discusses regional development patterns in China and examines effective ways of using development aid to attain regional balanced growth through optimizing growth spillover effects. Based on provincial panel data from 1978-99 she constructs an indicator "neighborhood performance" to measure the geographic spillover effects of aggregate growth from and to different provinces according to their relative richness and geographic position. Analysis of a Solow-type growth model suggests that positive spillover effects dominate negative shadow effects at the national level as well as the regional level, and some coastal provinces provide growth pull and growth push forces for their neighbors and serve as locomotives. The results show that the rapid takeoff of the coastal provinces has the largest spillover effects on the Chinese economy, but at the expense of a widening regional gap. A policy of encouraging the growth of the non-coastal regional hubs would have strong forward and backward linkages with the inland and western regions and thus reduce the regional development gap without sacrificing much aggregate growth. The author offers support for the policy of developing inland hubs, and argues that directing development aid to Hubei and Sichuan would optimize the growth spillover impacts on inland regions.